Pengaruh Terpaan Konten dan E-wom di Instagram terhadap Loyalitas Konsumen McDonald Indonesia pada Isu Pemboikotan - Sugiarto, Balqista Adillah (Jurnal Mahardika Adiwidia, 2024)
This research aims to examine the influence of Instagram content exposure and electronic word-of-mouth (e-WOM) on consumer loyalty towards McDonald's Indonesia, specifically amidst boycott issues. The theoretical framework guiding this study is Social Judgment Theory. Employing an explanatory quantitative method, non-probability sampling was conducted using purposive techniques to select participants who met predefined criteria. Questionnaires were administered to 160 active followers of the @mcdonaldsid Instagram account, all of whom were exposed to boycott-related content and specifically engaged with the "Mekdi for Humanity" campaign. The findings from hypothesis testing reveal the following insights: 1) Exposure to the "Mekdi Untuk Kemanusiaan" content significantly influences consumer loyalty towards McDonald's Indonesia amid boycott issues. 2) Conversely, e-WOM does not demonstrate a significant impact on consumer loyalty in the context of boycotts at McDonald's Indonesia. 3) The combined effect of exposure to "Mekdi Untuk Kemanusiaan" content and e-WOM on Instagram on Indonesian consumers' loyalty towards McDonald's amid boycott issues is observable, contributing 6.3% directly, while 93.7% of the variability is attributable to external factors beyond the scope of this study.